2022
DOI: 10.3390/toxics11010003
|View full text |Cite
|
Sign up to set email alerts
|

Microplastics in the Surface Water and Gastrointestinal Tract of Salmo trutta from the Mahodand Lake, Kalam Swat in Pakistan

Abstract: Microplastic pollution is becoming an increasingly severe environmental problem. As compared to the marine ecosystem, freshwater ecosystems at high-altitude, remote regions are less studied and lag far behind. Thus, the present study aims to highlight this issue and fill the gap in this regard. The presence of microplastics (MPs) in the surface water and the gastrointestinal tracts (GITs) of brown trout (Salmo trutta) from Lake Mahodand, Kalam Swat, Pakistan, at a high altitude of 2865 m above sea level was in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 66 publications
1
17
0
1
Order By: Relevance
“…This implies the significant variability of MP even for samples taken from locations in proximity, probably due to factors such as human activities and water flow, which demonstrate significant spatial and temporal variations. The lakes near the northeastern border of Kazakhstan and the northwest of Mongolia recorded a mean MP concentration of 11 ± 7 items/l [17], while Mahodand Lake in the northeast vicinity of Afghanistan contained a mean of 2.3 ± 1.52 MP/l [20]. The latter, though located remotely, is, in fact, a tourist spot.…”
Section: Abundance Of Mpmentioning
confidence: 95%
See 2 more Smart Citations
“…This implies the significant variability of MP even for samples taken from locations in proximity, probably due to factors such as human activities and water flow, which demonstrate significant spatial and temporal variations. The lakes near the northeastern border of Kazakhstan and the northwest of Mongolia recorded a mean MP concentration of 11 ± 7 items/l [17], while Mahodand Lake in the northeast vicinity of Afghanistan contained a mean of 2.3 ± 1.52 MP/l [20]. The latter, though located remotely, is, in fact, a tourist spot.…”
Section: Abundance Of Mpmentioning
confidence: 95%
“…However, with Iran sharing the southern perimeter of the Caspian Sea, few studies on the southern Caspian Sea were conducted near the southwestern border of Turkmenistan [18,19]. Similarly, for Afghanistan, a study was conducted for the Mahodand Lake of Pakistan, near its northeastern border [20].…”
Section: Abundance Of Mpmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that deteriorated polymer structures have a greater biological activity [42] due to the increased leaching of endocrine-disrupting chemicals produced from plastic and their capacity to interfere with energy metabolism. According to a field study by Bilal et al [43], up to thirty percent of persons have plastic in their gastrointestinal systems. Similarly, Prakash et al [44] found that Japanese medaka exposed to mm-sized polyethylene particles exhibited early indicators of endocrine disruption.…”
Section: Effect Of Polyethylene On Endocrine Systemsmentioning
confidence: 99%
“…In recent times, a number of studies have appeared that analyzed for MP concentrations in different environmental compartments in Pakistan, predominately in aquatic environments such as in nearshore waters (Ahmed et al, 2022), and along the coastline of the Arabian Sea (Ahmed et al,, 2022;Akhter and Panhwar, 2022;Arshad et al, 2023), but also in relatively secluded lakes such as the Mahodand Lake, Swat, Khyber Pakhtunkhwa District (Bilal et al, 2023) and Rawal Lake, Margalla Hills, Islamabad Capital territory (Nousheen et al, 2022;Irfan et al, 2020). MP concentrations were found to be signi cant.…”
Section: Introductionmentioning
confidence: 99%